[OP.5C.08] BLOOD PRESSURE PHENOTYPE AS A DETERMINANT OF AORTIC PULSE WAVE VELOCITY IN CHILDREN AND ADOLESCENTS - THE PORTUGUESE VASCULAR PHENOTYPE IN CHILDREN AND ADOLESCENTS COHORT. (September 2017) - Maldonado, J.; Pereira, T.; Martins, J.; Carvalho, M.
Abstract : Objective: The PORT-VASPh Cohort was designed to contribute to a better understanding of vascular function in children and adolescents, mostly focusing PWV and other complementary aspects of arterial hemodynamics. This preliminary analysis is aimed at analyzing the PWV as a function of the individual blood pressure (BP) phenotype. Design and method: Prospective and observational study, with 402 children and adolescents enrolled so far, 40% females, age ranging from 5 to 17 years (mean age: 11.81 ± 2.91 years). About 19.2% had family history of cardiovascular disease and overweight and at-risk weight classification accounted respectively for 7% and 12.2%. The overall health profile for each participant was defined based on three clinical evaluations, in which blood pressure (BP) was measured under standard conditions over the brachial artery with a clinically validated automatic sphygmomanometer (OMRON 705IT) and an appropriately sized cuff. Gender-specific percentiles were used for the definition of the individual BP phenotype. Carotid-femoral PWV was measured to all participants at the third clinical evaluation, with the Complior SP device, complying with the methodological recommendations. All participants were evaluated by the same experienced clinician. Results: Mean systolic (SBP) and diastolic (DBP) blood pressure were 116 ± 13 mmHg and 66 ± 9 mmHg, respectively. Mean heart rate (HR) was 70.21 ± 16.03 bpm. Mean PWV was 6.26 ± 1.02 m/s. BP distribution was 26.6% hypertensive (Ht), of which 16.4% stage 1, 10.2% stage 2, 10.7% high-normal, and 62.7% normal. The majority of the Ht presented isolated systolic (ISH) Ht (26.3%), with 4.3% presenting systolic-diastolic (SDH) Ht, and 2.5% isolated diastolic (IDH) Ht. Mean PWV was higher in Ht compared with normotensive (6.6 ± 1.0 m/s versus 6.1 ± 0.9 m/s, respectively; p < 0.001), and a significant increase in PWV was observed in accordance with the classification of BP: normal- 6.07 ± 0.96m/s; high-normal- 6.47 ± 1.07; stage 1 Ht- 6.6 ± 1.02; stage 2 Ht-6.7 ± 1.10; p = 0.001 for trend. PWV was also significantly higher in ISH compared with SDH and IDH (6.6 ± 1.1 versus 6.3 ± 0.89 versus 6.3 ± 0.94, respectively; p = 0.04). Conclusions: In children and adolescents, aortic PWV is strongly influenced by the BP phenotype, with an increase in PWV for higher stages of the BP classification and particularly associated with ISH.